3D printing is set to improve the efficiency of spiral-wound RO membranes. Issue 10 (October 2021) - Unknown
Abstract : Additive manufacturing, or 3D printing technology, is being used to dramatically improve the efficiency of spiral-wound RO membrane elements – minimising fouling potential and reducing capital and operational costs.